Strategiczna litygacja w czasie historycznego pożaru : przypadek Polski po roku 2015 - Wojtanowski, Mateusz (2022)
The article deals with the issue of strategic litigation in the time of historical dismay — a term which refers to the current time, characterized by, inter alia, the decline of a stable axiological framework for law-related practices in Polish society. First, I discuss strategic litigation and historical dismay. Then, the notion of political and legal culture as proposed by Paweł Jabłoński and Przemysław Kaczmarek is depicted and developed. I suggest supplementing the above-mentioned authors’ concept of the limits of juristic powers with an additional element: the primary choice relationship. Finally, I present conclusions on the impact of historical dismay on the limits of juristic powers and the peculiarity of strategic litigation. The problem of the further perspectives of liberalism is also addressed.
Keywords: culture; liberalism; the political; strategic litigation; legal interpretation; application of law; populism; human rights